Photon counting CT of the liver with dual-contrast enhancement - Muenzel, Daniela; Proksa, Roland; Daerr, Heiner; Fingerle, Alexander A.; Pfeiffer, Franz; Rummeny, Ernst J.; Noel, Peter B. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2016)
The diagnostic quality of photon counting computed tomography (PCCT) is one the unexplored areas in medical imaging; at the same time, it seems to offer the opportunity as a fast and highly sensitive diagnostic tool. Today, conventional computed tomography (CT) is the standard imaging technique for diagnostic evaluation of the parenchyma of the liver. However, considerations on radiation dose are still an important factor in CT liver imaging, especially with regard to multi-phase contrast enhanced CT. In this work we report on a feasibility study for multi-contrast PCCT for simultaneous liver imaging at different contrast phases. PCCT images of the liver were simulated for a contrast-enhanced examination performed with two different contrast agents (CA), iodine (CA 1) and gadolinium (CA 2). PCCT image acquisition was performed at the time point with portal venous contrast distribution of CA 1 and arterial contrast phase for CA 2. Therefore, a contrast injection protocol was planned with sequential injection of CA 1 and CA 2 to provide a time dependent difference in contrast distribution of both CAs in the vessels and parenchyma of the liver. Native, arterial, and portal venous contrast enhanced images have been calculated based on the spectral separation of PCCT. In simulated PCCT images, we were able to differentiate between the tissue enhancement of CA 1 and CA 2. The distribution of both CA within the parenchyma of the liver was illustrated with perfusion maps for CA 1 and CA 2. In addition, virtual noncontrast enhanced image were calculated. In conclusion, multi-phase PCCT imaging of the liver based on a single scan is a novel approach for spectral PCCT imaging, offering detailed contrast information in a single scan volume and a significant reduction of radiation dose.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dual Contrast; Liver Imaging; Material Decomposition; Photon Counting CT